Future Time Perspective in the Work Context: A Systematic Review of Quantitative Studies - Henry, Hélène; Zacher, Hannes; Desmette, Donatienne (Frontiers in Psychology, 2017)
A core construct in the lifespan theory of socioemotional selectivity, future time perspective (FTP) refers to individuals’ perceptions of their remaining time in life. Its adaptation to the work context, occupational future time perspective (OFTP), entails workers’ perceptions of remaining time and opportunities in their careers. Over the past decade, several quantitative studies have investigated antecedents and consequences of general FTP and OFTP in the work context (i.e., FTP at work). We systematically review and critically discuss this literature on general FTP (k = 17 studies) and OFTP (k = 16 studies) and highlight implications for future research and practice. Results of our systematic review show that, in addition to its strong negative relationship with age, FTP at work is also associated with other individual (e.g., personality traits) and contextual variables (e.g., job characteristics). Moreover, FTP at work has been shown to mediate and moderate relationships of individual and contextual antecedents with occupational well-being, as well as motivational and behavioral outcomes. As a whole, findings suggest that FTP at work is an important variable in the field of work and aging, and that future research should improve the ways in which FTP at work is measured and results on FTP at work are reported.